Value platform evolution in service innovation ecosystems: an examination of the dynamism of tensions resulting from co-existing institutional logics - Huang, Ying-Jia (2022)
Advanced technologies assist diverse entities in becoming network actors, exchanging resources and co-creating value together to achieve service innovation. However, tensions emerge when multiple actors have different goals and expectations during the service innovation process. This thesis extends the service ecosystems literature by incorporating the evolution of value platforms in the service innovation process over time. The notion of value platforms facilitates our understanding of the dynamic interactions among actors to co-create value for the development of service innovation. The theoretical lens of institutional logics was applied in this study to explore the dynamic resource-related activities that occur as value platforms evolve. This thesis explores the evolution of value platforms embedded in service ecosystems during the service innovation process. It investigates how the resource-related activities evolve in service ecosystems throughout the process of service innovation and seeks to unravel the mechanism of actor interaction in platform-based service innovation. In particular, the study investigates how value platforms embedded in service ecosystems evolve, what tensions arise throughout the evolution due to the multiple institutional logics of the actors within the ecosystem, and how multiple institutional logics are navigated as value platforms evolve. A critical realist approach is adopted to explore the phenomenon of value platform evolution. A process-based single-case study design with two embedded cases is implemented to investigate value platforms embedded in service ecosystems to develop telematics insurance services. The researcher conducted a two-phased data collection to gather semi-structured interviews and participant-generated drawings as primary data from different actors along with archival documents as the secondary data. A realist evaluation enabled the delineation of the five stages that form the building blocks of the evolution of the value platforms. Moreover, an abductive approach identified three types of process-related tensions and three types of navigating mechanisms that emerge dynamically as value platforms evolve. This research offers theoretical contributions to a processual understanding of value co-creation in service ecosystems by explaining the evolution of tensions resulting from co-existing institutional logics and navigating mechanisms inherent in value platforms. It also highlights how regulatory actors affect service ecosystems during the process of service innovation. Furthermore, the study offers practitioners a processual understanding of tensions that occur in the service innovation process, and the approaches to navigating those tensions in service ecosystems during the service innovation process.